Involvement of Anion-Specific Effects in Changes in the Gelation and Thermodynamic Properties of Calcium Alginate Hydrogel - Yuqiao Wang; Lin Li; Jiacheng Liu; Jianan Yan; Ce Wang; Bin Lai; Yu Dong; Haitao Wu (Foods, 2025)
The gelation process and hydrogel properties of calcium salt-induced alginate hydrogels are influenced by anion-specific effects. In this study, we investigated the effects of CaSO4, CaI2, and Ca(C5H9O3)2 [calcium β-hydroxy-β-methylbutyrate, CaHMB] on the gelation behavior of alginate hydrogels, using various mannuronic/guluronic acid (M/G) ratios to elucidate the underlying mechanisms of anion-specific effects. Here, at a high M/G ratio (2:1), the gelation time of CaSO4, as a low-solubility calcium source, delayed the formation of the calcium alginate hydrogel. The gelation time was 1.8 times that of the high-solubility calcium source CaHMB. Strongly hydrated ions (such as SO42− and C5H9O3−) caused the removal of water molecules from polysaccharide chains, resulting in the formation of small pores on the pore wall. Moreover, weakly hydrated chaotropic anions (I−) promoted the binding of alginate polysaccharide chains and water molecules, resulting in the slower thermal decomposition of water inside the gel. However, when the M/G ratio was reduced to 1:1 or 1:2, the influence of the three calcium salts on the water and thermodynamic properties of the hydrogels decreased, indicating that the anion-specific effect weakened. This study highlights the importance of anion-specific effects on the properties of alginate hydrogels and provides insights into the utilization of these effects to fabricate functional hydrogels with variable properties.